MANAGEMENT EDUCATION IN THE ERA OF A DIGITAL COMMUNITY - Muid, Abdul; Magfiroh, Magfiroh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The digital era is marking a new era that requires humans to think more pragmatically, because this era requires humans to always learn and update in carrying out activities faster and more concisely. If this era is not captured properly, it will make people miss the latest information.Including how we are good at managing the world of education, quickly and accurately, all developments in the world are accompanied by internet technology, sending any data, we use it by managing data by the internet. All aspects of life will change, because of the internet, human life is without the slightest limit. Both the old, the young, the small, everything will be driven by the development of the internet. So parents must be aware of today's digital era, because if parents are careless about our children's toys, then we will not know what their children are playing. our children in cyberspace. Even though there are positive and negative influences, if we are not good at monitoring it will be very dangerous, yes if what our children play has a positive value, then our children will be very smart, but if what our children play should be , then our children will be negatively affected by the shows our children see.In the context of the world of education, learning in the digital era demands teachers, lecturers, as educators who can follow the very fast developments in science and technology to foster critical thinking in students and students. Teachers and lecturers must look for issues related to the surrounding technology and the needs of students, students and issues of everyday life. Students can use relevant concepts to solve problems creatively independently under the guidance of a professional tutorial.Management of education in this digital era is very vital for the development of students, from the elementary school level to the tertiary level, and of course assisted by professional educators who keep up with the times, so that the knowledge conveyed to students is conveyed in a coherent and clear manner as well as being able to make students become qualified.